Consulta de enfermagem na área materno-infantil: estudo descritivo dos procedimentos em centros municipais de saúde na cidade do Rio de Janeiro - Mota, Sonia Maria Cantídio (1980)
Nursing Consultation is an activity institutionalized recently in Centess of Rio de Janeiro City particularly developed in Prenatal and Pediatric areas .The principal purpose of this descriptive study was verify the procedures followed by nurses in this pioneer work, also the assistance received by the Clientele, in order to offer contribution to accomplish or improve such an activity . The research have been developed through questionnaires with twelve nurses of six selected Health Centers with seventy five Clients of Prenatal and Pediatric consultations rooms .The results showed that the nurses ability for consultation and procedures is still precarious, evidencing that íbis activity continues directly United to institutions routine, showing reason for suggestions for its more efficacy and better quality .